This I Believe - Liggett, Carr (Tufts Archival Research Center, 2006)
Carr Liggett describes his belief that Jesus' Gospel is the way to happiness, and his uncertainities regarding the faith of his parents, as well as his beliefs in the importance of freedom, in accepting life and the world as we find it, and in tolerating and understanding others.